Edukasi Resusitasi Jantung Paru Pada Masyarakat Kabupaten Belitung: Edukasi Resusitasi Jantung Paru Pada Masyarakat Kabupaten Belitung - Ashar Abilowo; Astri Yulia Sari Lubis (Yayasan Ahmad Mansyur Nasirah, 2022)
The high prevalence of heart disease in Indonesia makes the introduction of Cardiopulmonary Resuscitation (CPR) to prevent worsening of the patient's condition before or after respiratory and cardiac arrest. Prevention is a series of efforts and anticipations that need to be considered before providing treatment for cardiac arrest or respiratory arrest. Prevention will give much better results than having to perform cardiopulmonary resuscitation. The purpose of this community service is to provide CPR education to youth in the Belitung Regency community by increasing the knowledge and skills of basic life support for ordinary people. The method in implementing this service goes through several stages, namely first, by reviewing the location to be addressed, taking care of licensing to the puskesmas and village office, and then conducting discussions with the puskesmas and village heads of Air Selumar and Pelepak Pute. The results after being given CPR education and practice with the demonstration method using phantom CPR, there was an increase in community knowledge by 86.7%. Education about CPR is needed by the community to improve knowledge and basic life support skills for ordinary people.